Preparation method of bamboo-based activated carbon composite electrode material
The composite of bamboo-based activated carbon with ZnCo2O4/ZnO/CoO by hydrothermal calcining method solves the problem of insufficient electrochemical performance of bamboo-based activated carbon and significantly improves the energy density and performance of supercapacitors.
Patent Information
- Application Number
- CN202411561361.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-07
AI Technical Summary
The electrochemical properties of existing bamboo-based activated carbon materials (such as specific capacitances) are relatively low, limiting their application in high-performance supercapacitors.
By preparing bamboo-based activated carbon composite electrode material, the bamboo-based activated carbon is compounded with ZnCo2O4/ZnO/CoO by hydrothermal calcining method, which significantly improves the specific capacitance of the electrode material.
The energy density and performance of the supercapacitor are significantly improved, and the specific capacitance of bamboo-based activated carbon composite electrode material has been improved from 193F/g to 687F/g.
Smart Images

Figure CN119400609A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of activated carbon modification, and in particular relates to a method for preparing a bamboo-based activated carbon composite electrode material. Background Art
[0002] Among different energy storage technologies, supercapacitors have become the leaders of energy storage devices due to their excellent charge and discharge capabilities, high power density and excellent stability. These characteristics enhance the potential application value of supercapacitors in various fields, such as flexible and wearable electronics. However, the electrochemical performance of supercapacitors mainly depends on the electrode materials. Among the various choices of environmentally friendly electrode materials, biomass activated carbon, as a cost-effective and abundant electrode material, is highly regarded for electrochemical double-layer capacitors because of its high specific surface area, efficient charge storage capacity, good pore size distribution and hierarchical structure, fast ion transport, relatively moderate conductivity, chemical and thermal stability, etc.
[0003] As a biomass carbon material, bamboo-based activated carbon has rich microporous structure and high specific surface area, which has attracted extensive attention in the research of supercapacitor electrode materials. The preparation process of traditional bamboo-based activated carbon electrode materials generally includes carbonization and activation of bamboo. However, although bamboo-based activated carbon has a high specific surface area and rich pore structure, its electrochemical properties (such as specific capacitance) are relatively low, which limits its application in high-performance supercapacitors. Summary of the invention
[0004] In order to solve the problem of insufficient electrochemical performance of existing bamboo-based activated carbon materials, the present invention provides a method for preparing a bamboo-based activated carbon composite electrode material. The bamboo-based activated carbon composite electrode material prepared by the method has a higher specific capacitance. Applying the bamboo-based activated carbon composite electrode material to manufacture supercapacitors can significantly improve the energy density and performance of supercapacitors.
[0005] The invention also provides a bamboo-based activated carbon composite electrode material.
[0006] The present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for preparing a bamboo-based activated carbon composite electrode material, the preparation method comprising:
[0008] Dissolving Zn(CH3COO)2 and Co(CH3COO)2 together in an organic solvent to obtain a mixed solution;
[0009] Dispersing bamboo-based activated carbon in water to obtain a dispersion liquid, and adding the dispersion liquid to the mixed liquid to obtain a reaction liquid;
[0010] The reaction solution is reacted at 180° C. for a period of time, and after cooling, the precipitate obtained by the reaction is washed and dried to obtain a reactant;
[0011] Under an inert atmosphere, the reactants are calcined at 350±2° C. for 2±0.1 h, and then the calcined products are ground to obtain a bamboo-based activated carbon composite electrode material.
[0012] Furthermore, the Zn(CH3COO)2 and Co(CH3COO)2 are dissolved together in an organic solvent to obtain a mixed solution, which specifically includes:
[0013] Zn(CH3COO)2 and Co(CH3COO)2 were dissolved in (CH2OH)2 at a molar ratio of 1:2 to obtain a mixed solution.
[0014] Optionally, the molar concentration of Zn(CH3COO)2 in the mixed solution is 0.0199 to 0.0201 mol / L.
[0015] Furthermore, the bamboo-based activated carbon is dispersed in water to obtain a dispersion liquid, and the dispersion liquid is added to the mixed liquid to obtain a reaction liquid, specifically comprising:
[0016] The bamboo-based activated carbon is dispersed in water to obtain a dispersion liquid, and the dispersion liquid is added to the mixed liquid, and the mixture is dissolved by stirring and ultrasonication to obtain a reaction liquid.
[0017] Furthermore, in the dispersion, the mass fraction of the bamboo-based activated carbon is 0.199-0.201%;
[0018] The volume ratio of the dispersion liquid to the mixed liquid is 1:1.
[0019] Further, the reaction solution is reacted at 180° C. for a period of time, and after cooling, the precipitate obtained by the reaction is washed and dried to obtain a reactant, which specifically includes:
[0020] The reaction solution is reacted at 180° C. for 3 to 12 hours. After cooling, the precipitate obtained by the reaction is washed with water and ethanol respectively, and then dried at 80±1° C. for 12±0.2 hours to obtain a reactant.
[0021] Preferably, the reaction solution is reacted at 180° C. for 9 hours, and after cooling, the precipitate obtained by the reaction is washed with water and ethanol respectively, and then dried at 80° C. for 12 hours to obtain a reactant.
[0022] Furthermore, the reactant is calcined at 350±2° C. for 2±0.1 h under an inert atmosphere, and the calcined product is then ground to obtain a bamboo-based activated carbon composite electrode material, which specifically comprises:
[0023] Under an inert atmosphere, the reactants were calcined at 350±2°C for 2±0.1h with a heating rate of 2°C / min, and the calcined products were then ground to obtain bamboo-based activated carbon composite electrode materials with a particle size of 60 to 100 μm.
[0024] Based on the same inventive concept, the present invention provides a bamboo-based activated carbon composite electrode material, and the bamboo-based activated carbon composite electrode material is prepared by the above-mentioned method for preparing a bamboo-based activated carbon composite electrode material.
[0025] Based on the same inventive concept, the present invention provides an application of a bamboo-based activated carbon composite electrode material in the preparation of a supercapacitor electrode.
[0026] Based on the same inventive concept, the present invention also provides a supercapacitor, which contains the above-mentioned bamboo-based activated carbon composite electrode material.
[0027] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0028] 1. The present invention discloses a method for preparing a bamboo-based activated carbon composite electrode material. The method composites bamboo-based activated carbon with ZnCo2O4 / ZnO / CoO through a hydrothermal calcination method, which significantly improves the specific capacitance of the electrode material. The method is applied to the manufacture of supercapacitors, which can significantly improve the energy density and performance of supercapacitors. On the other hand, the hydrothermal calcination method has a simple preparation process, is easy to mass produce, and has simple hydrothermal conditions, and the loading of metal oxides can be controlled and achieved by adjusting the hydrothermal conditions.
[0029] 2. The present invention discloses a bamboo-based activated carbon composite electrode material, which has higher specific capacitance and better electrochemical performance. When ordinary bamboo-based activated carbon is used to manufacture electrodes for supercapacitors, the specific capacitance is 193 F / g when the current density of constant current charge and discharge is 1 A / g in a voltage window of 0 to 0.6 V under a three-electrode system. The specific capacitance of the ZnCo2O4 / ZnO / CoO@bamboo-based activated carbon prepared by the present invention under the same conditions reaches 687 F / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 (a) XRD diffraction patterns of activated carbon with different hydrothermal times;
[0032] Figure 1 (b) Cyclic voltammogram of the composite electrode prepared when the hydrothermal time is 9 h;
[0033] Figure 1 (c) is the constant current charge-discharge diagram of the composite electrode prepared when the hydrothermal time is 9 h;
[0034] Figure 1 (d) is a comparison of cyclic voltammograms of different samples;
[0035] Figure 1 (e) is the cyclic voltammogram of the composite electrode prepared by direct mixing through ball milling;
[0036] Figure 1 (f) is the constant current charge-discharge diagram of the composite electrode prepared by direct mixing through ball milling;
[0037] Figure 1 (g) is the statistical diagram of specific capacitance. DETAILED DESCRIPTION
[0038] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0039] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0040] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0041] The technical principles of the present invention are as follows:
[0042] The present invention provides a method for preparing a bamboo-based activated carbon composite electrode material, the preparation method comprising:
[0043] S1. dissolving Zn(CH3COO)2 and Co(CH3COO)2 in an organic solvent to obtain a mixed solution;
[0044] S2. The bamboo-based activated carbon is dispersed in water to obtain a dispersion, and the dispersion is added to the mixed solution to obtain a reaction solution;
[0045] S3. reacting the reaction solution at 180° C. for a period of time, washing and drying the precipitate obtained by the reaction after cooling to obtain a reactant;
[0046] S4. Under an inert atmosphere, the reactants are calcined at 350±2°C for 2±0.1h, and then the calcined products are ground to obtain bamboo-based activated carbon composite electrode materials.
[0047] Step S1 specifically includes:
[0048] Zn(CH3COO)2 and Co(CH3COO)2 were dissolved in (CH2OH)2 at a molar ratio of 1:2 to obtain a mixed solution.
[0049] In the present invention, Zn(CH3COO)2 and Co(CH3COO)2 are dissolved in (CH2OH)2 at a molar ratio of 1:2. Since ZnCo2O4 has a high theoretical specific capacitance, a multi-component oxide mainly composed of ZnCo2O4 can be formed by controlling the molar ratio to 1:2, thereby maximizing the pseudocapacitance contribution; and the co-dissolution method helps to improve the uniformity of the reactants, ensure the consistency of the generated composite oxide in microstructure, and improve the overall performance of the material. If the molar ratio is lower than 1:2, it will cause Zn 2+ The relative lack of ZnCo2O4 affects the formation of ZnCo2O4, forming a multi-element oxide mainly composed of ZnO, which reduces the specific capacitance contribution of the material. 2+ Concentration may lead to decreased uniformity of the product and increase the risk of phase separation, which in turn affects the stability and performance of the final material. If the molar ratio is higher than 1:2, it may lead to 2+ The excess of CoO forms by-products such as CoO, thus affecting the formation of ZnCo2O4.
[0050] Optionally, the molar concentration of Zn(CH3COO)2 in the mixed solution is 0.0199 to 0.0201 mol / L.
[0051] In the present invention, the molar concentration of Zn(CH3COO)2 in the mixed solution is 0.0199-0.0201 mol / L, which helps to ensure that Zn 2+ Ions and Co 2+ The ions react in a designed 1:2 molar ratio, thereby promoting the formation of the desired products (ZnCo2O4, ZnO, CoO) and ensuring that the structure and chemical properties of the composite material meet expectations; on the other hand, within this concentration range, the reactants can be fully dissolved and evenly distributed in the solution, which helps to reduce the generation of by-products and material inhomogeneity.
[0052] Step S2 specifically includes:
[0053] The bamboo-based activated carbon is dispersed in water to obtain a dispersion liquid, and the dispersion liquid is added to the mixed liquid, and the mixture is dissolved by stirring and ultrasonication to obtain a reaction liquid.
[0054] Furthermore, the mass fraction of the bamboo-based activated carbon is 0.199-0.201%;
[0055] The volume ratio of the dispersion liquid to the mixed liquid is 1:1.
[0056] Step S3 specifically includes:
[0057] The reaction solution is reacted at 180° C. for 3 to 12 hours. After cooling, the precipitate obtained by the reaction is washed with water and ethanol respectively, and then dried at 80±1° C. for 12±0.2 hours to obtain a reactant.
[0058] In the present invention, the advantage of reacting the reaction solution at 180°C for 3 to 12 hours is that 180°C is the temperature for the formation of ZnCo2O4, and a reaction temperature below 180°C is not conducive to the formation of ZnCo2O4, which may result in a decrease in the specific capacitance of the formed composite material; a reaction temperature above 180°C will increase energy consumption, thereby increasing the cost of the entire preparation process, especially in large-scale production, the increase in energy consumption will lead to a decrease in economic benefits; and a higher temperature may have a certain impact on the activated carbon structure itself.
[0059] In the present invention, water and ethanol are used to wash the precipitate obtained by the reaction, respectively. Deionized water can effectively remove water-soluble impurities in the reaction process, such as unreacted metal salts, acids, alkalis and other inorganic compounds. The organic solvent properties of ethanol can help remove organic impurities or by-products, especially organic ligands or additives that may remain in the reaction process, such as (CH2OH)2 in this experiment. At the same time, ethanol is highly volatile, which is convenient for quickly drying the precipitate.
[0060] Step S4 specifically includes:
[0061] Under an inert atmosphere, the reactants were calcined at 350±2°C for 2±0.1h with a heating rate of 2°C / min, and the calcined products were then ground to obtain bamboo-based activated carbon composite electrode materials with a particle size of 60 to 100 μm.
[0062] In the present invention, the reactants are calcined at 350±2℃ for 2±0.1h. The benefits are as follows: at a calcination temperature of about 350℃, the crystal phase formation of ZnCo2O4, ZnO and CoO can be effectively promoted, ensuring that the composite oxide has a good crystal structure and electrochemical activity; the temperature condition is relatively moderate, which can effectively prevent excessive sintering (agglomeration or excessive growth) of particles, thereby maintaining the nanostructure and good surface activity of the material; compared with higher temperatures, 350℃ is relatively low, which can reduce energy consumption and production costs while maintaining material properties. Too low a reaction temperature may result in poor crystal structure of composites such as ZnCo2O4, reducing the electrochemical activity and specific capacitance of the material; insufficient calcination may result in residual organic precursors or impurities, affecting the purity and performance of the electrode material; and too high a temperature may destroy the porous structure of the composite material, affecting its conductivity and energy storage performance, and may even induce side reactions; and higher temperatures not only increase energy consumption and production costs, but may also require more complex equipment and higher maintenance costs.
[0063] The purpose of carrying out the reaction under an inert atmosphere is to avoid reaction with oxygen in the air in an inert atmosphere (such as nitrogen, argon), prevent the formation of excessive oxides on the surface or inside the material, and ensure that the synthesized compound has the required oxidation state; prevent the activated carbon from reacting with the air to generate gas, thereby making it impossible to guarantee the composition ratio of the product; and improve the controllability of the reaction and reduce the occurrence of side reactions.
[0064] The preparation method of a bamboo-based activated carbon composite electrode material, the composite electrode material and its application are described in detail below in combination with embodiments and experimental data.
[0065] Example 1
[0066] The present embodiment provides a method for preparing a bamboo-based activated carbon composite electrode material, comprising the following steps:
[0067] (1) Zn(CH3COO)2·2H2O and Co(CH3COO)2·4H2O were weighed in a molar ratio of 1:2 and uniformly mixed in 50 mL of (CH2OH)2 to obtain a mixed solution (wherein the concentration of Zn(CH3COO)2 was 0.020 mol / L).
[0068] (2) Dissolve 0.100 g of bamboo-based activated carbon in 50 mL of deionized water.
[0069] (3) The mixed solution was placed on a magnetic stirrer and stirred for 1 h. During the stirring process, 50 mL of deionized water containing 0.100 g of bamboo-based activated carbon was gradually added, and then ultrasonicated for 30 min to dissolve.
[0070] (4) After dissolution, pour into a 150 mL reactor and react in a vacuum oven at 180 °C for 9 h.
[0071] (5) After cooling naturally, wash with deionized water and anhydrous ethanol several times and filter.
[0072] (6) The filtered precipitate was then placed in an 80° C. forced air drying oven and dried for 12 h to obtain a reactant.
[0073] (7) Finally, the reactants were placed in a tubular furnace and calcined at 350°C for 2 h (heating rate 2°C / min) under a N2 atmosphere. The calcined solid was ground to obtain a powdered ZnCo2O4 / ZnO / CoO@bamboo-based activated carbon composite material (where “ / ” represents “and”), which is the desired supercapacitor electrode material with a particle size of 60 to 100 μm.
[0074] In this example, the electrochemical properties of the material were tested by assembling a three-electrode system: the three-electrode system was assembled with 6M KOH as the electrolyte, platinum sheet as the counter electrode, and mercury / mercuric oxide as the reference electrode. Bamboo-based activated carbon (ZnCo2O4 / ZnO / CoO@bamboo-based activated carbon), acetylene black and PTFE emulsion were mixed in a mass ratio of 8:1:1 and pressed onto a nickel foam (1 cm 2 ) and the electrochemical test was carried out using the CorrTest electrochemical test system to test the linear cyclic voltammetry and constant current charge-discharge performance of the electrode material in the voltage window of 0 to 0.6 V.
[0075] Example 2
[0076] Zn(CH3COO)2·2H2O and Co(CH3COO)2·4H2O were weighed respectively according to a molar ratio of 1:2, and bamboo-based activated carbon was added for uniform ball milling and mixing to obtain a composite electrode material.
[0077] The electrochemical performance of the material was then tested by assembling a three-electrode system: the three-electrode system was assembled with 6M KOH as the electrolyte, platinum sheet as the counter electrode, and mercury / mercuric oxide as the reference electrode. The composite electrode material, acetylene black, and PTFE emulsion were mixed in a mass ratio of 8:1:1 and pressed onto a nickel foam (1 cm 2 ) and the electrochemical test was carried out using the CorrTest electrochemical test system to test the linear cyclic voltammetry and constant current charge-discharge performance of the electrode material in the voltage window of 0 to 0.6 V.
[0078] The test results of the composite electrode materials prepared in Examples 1 and 2 are as follows: Figure 1 shown.
[0079] according to Figure 1 (a) It can be seen that the ZnCo2O4 / ZnO / CoO@bamboo-based activated carbon composite material was successfully prepared. BFAC is bamboo-based activated carbon, and the composite materials prepared under different hydrothermal times are represented by the time used. Figure 1 As can be seen in (b), at different scan rates, its linear cyclic voltammogram shows a pair of redox peaks, which will shift with the increase of scan rate. The possible reason is that the diffusion rate of ions in the electrolyte may not be sufficient to keep up with the electrode reaction, resulting in a lag in the reaction, thus affecting the position of the peak. Figure 1 (c) is a graph showing the relationship between current density and time. It can be seen from the figure that the GCD curves at different current densities all have obvious reaction platforms, further confirming the occurrence of redox reactions.
[0080] like Figure 1 As shown in (d), by testing the linear cyclic voltammogram of the composite electrode material prepared at different hydrothermal times, it can be seen that the curve at a linear scan rate of 5mv / s has a pair of redox peaks, indicating pseudocapacitive properties. As a current collector, the capacitance behavior of nickel foam can be ignored and has little effect on the results. Therefore, the effect of nickel foam on the experimental results can be ignored. From the constant current charge and discharge curve and the relationship between specific capacitance and current density Figure 1 It can be seen from (g) that the electrode prepared by using bamboo-based activated carbon has a specific capacitance of 193F / g when the current density of constant current charge and discharge is 1A / g in the voltage window of 0-0.6V under the three-electrode system, while the highest specific capacitance of ZnCo2O4 / ZnO / CoO@bamboo-based activated carbon prepared in Example 1 under the same conditions is 687F / g.
[0081] The cyclic voltammetry and constant current charge and discharge of the composite electrode material prepared in Example 2 are shown in FIG. Figure 1 As shown in (e) and (f), it can be seen that it has pseudocapacitive properties. When the constant current is 1A / g, the specific capacitance is about 85F / g.
[0082] The possible reason is that in alkaline electrolyte, Zn(CH3COO)2·2H2O and Co(CH3COO)2·4H2O themselves do not have the ability to undergo redox reactions, and after physical mixing with BFAC, the proportion of activated carbon in the active material is changed, which greatly reduces the original performance compared with BFAC. The reason why ZnCo2O4 / ZnO / CoO@BFAC has good electrochemical performance may be that Zn(CH3COO)2·2H2O and Co(CH3COO)2·4H2O are converted into ZnCo2O4, ZnO and CoO that can undergo redox reactions through hydrothermal method, and can grow on BFAC after hydrothermal treatment, which greatly increases their mutual binding ability compared with the physical mixing method, and increases the specific capacitance through the reaction as shown in the following reaction equation.
[0083]
[0084] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0085] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0086] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a bamboo-based activated carbon composite electrode material, characterized in that: The preparation method comprises: Dissolving Zn(CH3COO)2 and Co(CH3COO)2 together in an organic solvent to obtain a mixed solution; Dispersing bamboo-based activated carbon in water to obtain a dispersion, and adding the dispersion to the mixed solution to obtain a reaction solution; The reaction solution is reacted at 180° C. for a period of time, and after cooling, the precipitate obtained by the reaction is washed and dried to obtain a reactant; Under an inert atmosphere, the reactants are calcined at 350±2° C. for 2±0.1 h, and then the calcined products are ground to obtain a bamboo-based activated carbon composite electrode material.
2. The method for preparing a bamboo-based activated carbon composite electrode material according to claim 1, characterized in that: The method of dissolving Zn(CH3COO)2 and Co(CH3COO)2 in an organic solvent to obtain a mixed solution specifically comprises: Zn(CH3COO)2 and Co(CH3COO)2 were dissolved in (CH2OH)2 at a molar ratio of 1:2 to obtain a mixed solution.
3. The method for preparing a bamboo-based activated carbon composite electrode material according to claim 2, characterized in that: The molar concentration of Zn(CH3COO)2 in the mixed solution is 0.0199-0.0201 mol / L.
4. The method for preparing a bamboo-based activated carbon composite electrode material according to claim 1, characterized in that: The method of dispersing bamboo-based activated carbon in water to obtain a dispersion liquid, and adding the dispersion liquid to the mixed liquid to obtain a reaction liquid specifically comprises: The bamboo-based activated carbon is dispersed in water to obtain a dispersion liquid, and the dispersion liquid is added to the mixed liquid, and the mixture is dissolved by stirring and ultrasonication to obtain a reaction liquid.
5. The method for preparing a bamboo-based activated carbon composite electrode material according to claim 4, characterized in that: In the dispersion, the mass fraction of the bamboo-based activated carbon is 0.199-0.201%; The volume ratio of the dispersion liquid to the mixed liquid is 1:
1.
6. The method for preparing a bamboo-based activated carbon composite electrode material according to claim 1, characterized in that: The reaction liquid is reacted at 180° C. for a period of time, and after cooling, the precipitate obtained by the reaction is washed and dried to obtain a reactant, which specifically includes: The reaction solution is reacted at 180° C. for 3 to 12 hours. After cooling, the precipitate obtained by the reaction is washed with water and ethanol respectively, and then dried at 80±1° C. for 12±0.2 hours to obtain a reactant.
7. The method for preparing a bamboo-based activated carbon composite electrode material according to claim 1, characterized in that: The reactant is calcined at 350±2° C. for 2±0.1 h under an inert atmosphere, and the calcined product is then ground to obtain a bamboo-based activated carbon composite electrode material, which specifically comprises: Under an inert atmosphere, the reactants were calcined at 350±2°C for 2±0.1h with a heating rate of 2°C / min, and the calcined products were then ground to obtain bamboo-based activated carbon composite electrode materials with a particle size of 60 to 100 μm.
8. A bamboo-based activated carbon composite electrode material, characterized in that: The bamboo-based activated carbon composite electrode material is prepared by a preparation method of a bamboo-based activated carbon composite electrode material according to any one of claims 1-7.
9. Use of a bamboo-based activated carbon composite electrode material as claimed in claim 8 in preparing supercapacitor electrodes.
10. A supercapacitor, characterized in that: The supercapacitor contains the bamboo-based activated carbon composite electrode material as described in claim 8.
Citation Information
Patent Citations
NiCo2O4 / active carbon composite material preparation method
CN106710891A
Carbonized silk fabric / transition metal oxide composite material for flexible lithium ion battery negative electrode and preparation method thereof
CN109713261A
Preparation method of high-performance NiCo2O4 / C composite material
CN111675250A
Method for preparing sodium-ion battery negative electrode material based on ZnCo2O4 / hollow carbon nanoring and application
CN115036502A